The Vietnam Lobby : the American Friends of Vietnam, 1955-1975. - Morgan, Joseph G. (The University of North Carolina Press, 2009)
Established in 1955 as a private advocacy group, the American Friends of Vietnam worked to influence U.S. attitudes and policies toward Vietnam for nearly two decades. AFV members wrote articles, gave speeches, sponsored aid drives, and forged ties with journalists, academics, and government officials in an effort to generate American assistance for South Vietnam. In The Vietnam Lobby, Joseph Morgan shifts the focus away from the much-examined antiwar demonstrations that took place in America to concentrate instead on the actions of those who endorsed U.S. intervention in Vietnam.